ANALISA KEPATUHAN WAJIB PAJAK ATAS IMPLEMENTASI NIK MENJADI NPWP - megasari, Sintya; Frederica, Diana (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
The government in Indonesia continues to reform policies to improve tax compliance, one of which is the implementation of the Population Identification Number (NIK) as the Taxpayer Identification Number (NPWP). Before the implementation of this policy, NPWP was issued separately from NIK. The registration process is often complex so that people delay registering themselves as taxpayers. Through the integration of NIK into NPWP, all people who have NIK will be automatically registered as taxpayers. This study aims to compare the level of tax compliance in terms of tax revenue, SPT reporting, the number of tax sanctions and the number of tax audits before, during the transition and after the implementation of NIK into NPWP at several Tax Service Offices in DKI Jakarta. The type of data used is secondary data obtained from tax service offices that have been submitted in previous e-research. The population used in this study are taxpayers in DKI Jakarta and with accesses that have been approved by e-research. The research method used is quantitative descriptive. Descriptive analysis is used to summarize the data that has been collected and the data is displayed in the form of graphs, tables or diagrams. The analysis results show that there are significant differences in most KPPs. However, several KPPs show no significant changes. This conclusion provides a more comprehensive picture of the impact of the NIK implementation policy as a NPWP on taxpayer compliance, as well as being the basis for evaluating future policies